Waste-to-energy : technologies and project implementation - Rogoff, Marc Jay.; Screve, Francois; ScienceDirect eBooks (Waltham, MA : William Andrew, 2011)
This book covers in detail programs and technologies for converting traditionally landfilled solid wastes into energy through waste-to-energy projects. Modern Waste-to-Energy plants are being built around the world to reduce the levels of solid waste going into landfill sites and contribute to renewable energy and carbon reduction targets. The latest technologies have also reduced the pollution levels seen from early waste incineration plants by over 99%. With case studies from around the world, Rogoff and Screve provide an insight into the different approaches taken to the planning and impl.
Front Cover; Waste-to-Energy; Copyright; Contents; Preface; About the Authors; Chapter 1 -Introduction and overview; Chapter 2 -Project implementation concepts; Chapter 3 -WTE technology; Chapter 4 -Solid waste composition and quantities; Chapter 5 -Waste flow control; Chapter 6 -Selecting the facility site; Chapter 7 -Energy and materials markets; Chapter 8 -Permitting issues; Chapter 9 -Procurement of WTE systems; Chapter 10 -Ownership and financing of WTE facilities; Chapter 11 -O & M of WTE facilities; Appendix A -WTE Case Studies; Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Refuse as fuel; Waste products as fuel; Incineration; Refuse and refuse disposal; TECHNOLOGY & ENGINEERING -- Power Resources -- General; BUSINESS & ECONOMICS -- Industries -- Energy; SCIENCE -- Energy; Incineration; Refuse and refuse disposal; Refuse as fuel; Waste products as fuel; Electronic books